Extreme two-phase change of ionospheric electron temperature overshoot during geomagnetic storms - Smirnov, Artem; Shprits, Yuri; Luehr, Hermann; Pignalberi, Alessio; Kronberg, Elena; Prol, Fabricio; Xiong, Chao (Springer, 2025)
An intense surge in the equatorial electron temperature (Te) at sunrise, known as the morning Te overshoot, has been one of the defining ionospheric features since its discovery early in the Space Age. Despite decades of study, the behavior of the morning overshoot during geomagnetic storms remains poorly understood. We report a two-stage response of the morning Te overshoot to geomagnetic activity, uncovered by a neural network model. Electron temperatures show an initial enhancement during the storm’s main phase, followed by a drastic depletion exceeding 1000 K and disappearance of the overshoot in the recovery phase. This two-phase change aligns with the early influence of westward prompt penetration electric field, overtaken by the development of the eastward disturbance dynamo later in the storm. These electric field changes affect vertical plasma drifts that redistribute electron densities, modifying ionospheric cooling rates. Our findings provide new insights into the dynamics of one of the most widely studied ionospheric features and showcase the potential of new-generation digital twin models of near-Earth space environment to reveal previously unrecognized physical patterns.
Keywords: Ionosphere; Electron temperature; Neural networks; fi=Tietotekniikka tekn|en=Information Technology tech|